TGHC: timed guarded Horn clauses - Saito, K. (Proceedings [1992] The Ninth TRON Project Symposium, 1992)
A description is given of the design principles, syntax, and semantics of the distributed real-time programming language TGHC (timed guarded Horn clauses). TGHC is a descendant of concurrent logic programming languages and it is capable of explicitly expressing time constraints by introducing the timed guard to GHC. A formal semantics of a subset of TGHC is also given.< >